The Role of Internal Corporate Governance Mechanism in Accounting Conservatism - Nur, Mardiani; Anugerah, Rita; Indrawati, Novita (Universitas Syiah Kuala, 2019)
AbstractObjective This study aims to analyze the influence of internal mechanisms (independent commissioner, ownership structure and audit committee) on accounting conservatism in mining companies listed on the Indonesia Stock Exchange for the period of 2015-2017.Design/methodology Secondary data in the form of financial statements are collected from the sub-sector companies in mining industry from the Indonesian capital market directory (ICMD). The data is taken from companies listed in Indonesia stock exchange for the period of 2015-2017. Samples are determined by using purposive sampling method and are selected based on certain considerations or criteria. The analysis model used in this study is path analysis.Results The results of this study prove that independent commissioners, ownership structures and audit committees have a positive effect on accounting conservatism.Research limitations/implications This study is perhaps limited in the number of variables used to test the model. There may be other variables that affect accounting conservatism so that further studies can extend this study by utilizing more variables.